(untitled) (Research, Society and Development, 2021)
The objective this work was to evaluate genetically the buffaloes populations using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) in the leptin and stearoyl-CoA desaturase (SCD) genes, and associate the genotypes with milk production. Sixty-nine samples of Bubalus bubalis - 38 Murrah breed, 18 Mediterranean and 13 mixed-breed of the Murrah with Mediterranean - were evaluated. Allele and genotype frequencies, the heterozygosity observed and expected, the inbreeding coefficients (FIS), the probabilities of the Hardy-Weinberg equilibrium, the F statistic for population differentiation and Shannon index were calculated using GENEPOP and GenALEx programs. The associations of the different genotypes with a role in milk production were tested by Analysis of Variance (ANOVA) and t-test. We reported the leptin and SCD allele contribution to genetic variability in buffaloes herds in the Brazilian Amazonian region. The A allele was more representative in leptin and SCD genes for all breed groups. No significant effects between genotypes and milk production were found in the present study, but there is an indicative that AA genotype in leptin gene affects milk production in Murrah breed.